Analysis of pharmaceutical market of dietary supplements with green tea leaves extract - O. Yu. Maslov; S. V. Kolisnyk; M. A. Komisarenko; S. M. Poluian; M. Yu. Holik; T. O. Tomarovska (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2022)
The aim of work is to study the assortment of dietary supplements with green tea leaves extract on the modern pharmaceutical market to further search for ways to improve and optimize pharmaceutical supply.